2020
DOI: 10.3390/jcm9061818
|View full text |Cite
|
Sign up to set email alerts
|

Always Online? Internet Addiction and Social Impairment in Psoriasis across Germany

Abstract: With the World Health Organization (WHO) demanding further investigation of the social impairment and psychosocial burden of psoriasis, a first study identified a high prevalence of Internet addiction. The aim of this study was to assess social impairment and estimate the occurrence of Internet addiction along with depression, cigarette smoking, and alcohol dependency in individuals with psoriasis recruited online in a people-centered care approach. A cross-sectional online survey was carried out across German… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
(63 reference statements)
0
10
0
1
Order By: Relevance
“…The study results, however, not only indicated a higher rate of Internet addiction in comparison to the general population, but also in comparison with two previous studies among people with psoriasis. For example, in a study among individuals with psoriasis reached via online self‐help groups the reported prevalence was 8.5% 12 and in a study among psoriasis patients recruited offline, in clinics and dermatological offices, the prevalence was 3.8% 11 . Therefore, the way affected individuals are reached seems to be essential for the frequency of positive screenings for Internet addiction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study results, however, not only indicated a higher rate of Internet addiction in comparison to the general population, but also in comparison with two previous studies among people with psoriasis. For example, in a study among individuals with psoriasis reached via online self‐help groups the reported prevalence was 8.5% 12 and in a study among psoriasis patients recruited offline, in clinics and dermatological offices, the prevalence was 3.8% 11 . Therefore, the way affected individuals are reached seems to be essential for the frequency of positive screenings for Internet addiction.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] First studies indicated that psoriasis is potentially associated with other addictive behaviors such as Internet addiction. 11,12 As Internet addiction represents a rapidly rising phenomenon of societies worldwide, the fifth edition of…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, internet access or connection speed might have been other covariates to explain the association between urban upbringing and CIU. Furthermore, chronic diseases such as psoriasis, which causes social impairment and a psychosocial burden might be confounders [ 35 ]. Fourth, a type 2 error may have happened because the number of people with severe CIU was a small percentage of the total sample size.…”
Section: Discussionmentioning
confidence: 99%
“…All of these factors taken altogether lead to social deterioration or the inability to start a family or cause the already existing family system to fall apart. It is well-reported that psoriatic patients have a lower ability to function in everyday life and create social bonds and have a disturbed sexual life ( 38 , 61 ). The impact of psoriasis on everyday existence is dependent on sex and age.…”
Section: Mutual Links Between Sleep Disorders In Psoriatic Patients and Their Quality Of Life And Psychosocial Statusmentioning
confidence: 99%